Mapping diurnal changes in choroidal, Haller’s and Sattler’s layer thickness using 3-dimensional 1060-nm optical coherence tomography - Gabriel, Maximilian; Esmaeelpour, Marieh; Shams-Mafi, Farnusch; Hermann, Boris; Zabihian, Behrooz; Drexler, Wolfgang; Binder, Susanne; Ansari-Shahrezaei, Siamak (Graefe's archive for clinical and experimental ophthalmology, 2017)
Purpose To test the significance of diurnal changes in choroidal, Haller’s and Sattler’s layer thickness in healthy subjects using spatial analysis of three-dimensional (3D) 1060-nm optical coherence tomography (OCT) scans. Methods Automatically generated choroidal, Haller’s and Sattler’s layer thickness maps were statistically analyzed for 19 healthy subjects at two time points (8 a.m. and 6 p.m.) that represent the currently proposed ChT peak and nadir. All subjects were imaged by high-speed 1060-nm OCT over a 36° × 36° field of view. Spatial distribution of layer thickness was analyzed using the Early Treatment Diabetic Retinopathy Study (ETDRS) grid. Results The choroid was significantly thicker at 8 a.m. than at 6 p.m. (p < 0,0125, paired t-test, Bonferroni correction). Diurnal variation of mean choroidal thickness (ChT) for all ETDRS subfields was 12 μm. Haller’s layer thickness showed no significant diurnal variation (P > 0.0125), but Sattler’s layer was thicker in the morning than in late afternoon (P < 0.0125). Conclusions Our measurements indicate that diurnal ChT variation may exist, but is less relevant than previously proposed by studies using single location imaging. Sattler’s layer shows diurnal variation in line with ChT.